New Insights into the Potential Cytotoxic Role of Bacillus cytotoxicus Cytotoxin K-1 - Klèma Marcel Koné; Pauline Hinnekens; Jelena Jovanovic; Andreja Rajkovic; Jacques Mahillon (Toxins, 2021)
The thermotolerant representative of the Bacillus cereus group, Bacillus cytotoxicus, reliably harbors the coding gene of cytotoxin K-1 (CytK-1). This protein is a highly cytotoxic variant of CytK toxin, initially recovered from a diarrheal foodborne outbreak that caused the death of three people. In recent years, the cytotoxicity of B. cytotoxicus has become controversial, with some strains displaying a high cytotoxicity while others show no cytotoxicity towards cell lines. In order to better circumscribe the potential pathogenic role of CytK-1, knockout (KO) mutants were constructed in two B. cytotoxicus strains, E8.1 and E28.3. The complementation of the cytK-1 KO mutation was implemented in a mutant strain lacking in the cytK-1 gene. Using the tetrazolium salt (MTT) method, cytotoxicity tests of the cytK-1 KO and complemented mutants, as well as those of their wild-type strains, were carried out on Caco-2 cells. The results showed that cytK-1 KO mutants were significantly less cytotoxic than the parental wild-type strains. However, the complemented mutant was as cytotoxic as the wild-type, suggesting that CytK-1 is the major cytotoxicity factor in B. cytotoxicus.